Embodiment, Myth, and Charactersâ Value Sculpture of Tau Tau at Toraja in South Sulawesi - Suherman, Suherman; Triyanto, Triyanto; Sunarto, Sunarto (Catharsis, 2017)
This research aims to study the embodiment sculpture Tau Tau in Toraja as a work of art, the urgency in Rambu Soloâ rituals, the myth, and the characterâs value contained in it. The approach used is descriptive qualitative which lead to ethnographic, with techniques of observation, interviews, and document study in collecting data. The results obtained in this study indicate that, First, the sculpture of Tau Tau in Toraja is a primitive which is monumental style, with an aesthetic that is mythic-religious. Second, the sculpture of Tau Tau is important in the Rambu Soloâ ritual for the nobility because it is one determinant of excellence ceremony. Third, the sculptures represent the Tau Tau from the myths that live in the minds of religious-arkhais communities Torajans, like the myth of Eran di Langiâ, the myth of the birth of Datu Laukku and Puang Adang, myths about Daeta-Daeta and myths about the end of human life. Fourth, the sculpture of Tau Tau contains character values, such as the attitude of respect, responsibility, wisdom, love and compassion, hard work, integrity, and a sense of gratitude. Based on the research results, put forward the suggestion that, First, the Department of Education and Culture need to incorporate sculpture Tau Tau into the learning materials in schools. Second, artists need to introduce more in sculpture Tau Tau through the studies. Third, citizens of Toraja societies which needs to have a high awareness of the importance of maintaining and preserving the sculpture Tau Tau as cultural products that few of their ancestors.